Douglas C. Harr letter to Thomas H. Kent regarding bird sightings, February 27, 1980 - Harr, Douglas C.et al (1980)
Field notes contributed by Douglas C. Harr in a letter to Thomas H. Kent, February 27, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed